The Role of Family Support Towards Perinatal Depression in Medan - Sitorus, Nopitayanti; Putri, Pratiwi Syah; br Kaban, Nurhaida (International Journal of Public Health Excellence (IJPHE), 2024)
Perinatal depression, commonly known as postpartum depression, is a serious complication of childbirth that can have significant adverse effects on both the mother and baby. It typically occurs 4-6 weeks after giving birth. Mothers require family and social support to cope with stress during the postpartum period, which is caused by sudden hormonal changes that affect mood swings, the burden of household work, and caring for the baby and mother. This can result in fatigue and lack of sleep. The research aims to analyze the impact of family and social support on the occurrence of depression. The study employed an analytical observational method with a cross-sectional approach to examine the population of postpartum mothers aged 0-6 weeks in the Sukoharjo District Health Service work area. The sample size consisted of 160 respondents selected through Multistage Random Sampling. The study utilized family support questionnaires, social support, and EPDS (Edinburgh Postnatal Depression Scale) as instruments. Logistic regression and Odd Ratio were used for data analysis. The data analysis results for family support yielded a P-value of 0.027 < (0.05) and an OR value of 5.787. The analysis for social support resulted in a P-value of 0.025 < (0.05) and an OR value of 5.693. These results indicate a significant influence of family and social support on the occurrence of DEPRESSION. Mothers who lack family and social support are at a higher risk of experiencing DEPRESSION, with a risk 5.787 and 5.693 times higher, respectively. Healthcare professionals should prioritize the significance of family and social support for postpartum mothers, providing both emotional and technical assistance. This includes aiding mothers in caring for their babies, self-care, and household tasks to mitigate the risk of postpartum depression.